The area of the square is given by the quadratic expression:
[tex]A = 9x^2 - 6xy + y^2[/tex]
If we have a square whose side measures S, the area of said square is given by the equation:
[tex]A = S^2[/tex]
In this case, we know that the side length of our square is given by:
[tex]S = 3x - y[/tex]
Replacing that in the area equation we get:
[tex]A = (3x - y)^2[/tex]
Now we just need to expand that product, we will get:
[tex]A = (3x - y)^2 = (3x)*(3x) + (3x)*(-y) + (-y)*(3x) + (-y)*(-y) \\\\A = 9x^2 - 6xy + y^2[/tex]
Then we can see that the correct option is the last one.
If you want to learn more about squares you can read:
https://brainly.com/question/24487155
#SPJ1